Pengaruh Efektivitas Pengendalian Internal, Moralitas Individu, Budaya Organisasi, Dan Kecerdasan Spiritual Terhadap Kecenderungan Kecurangan Akuntansi - I Kadek Alit Arinata; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2022)
Deception is a deliberate fallacy. In the scope of accounting, fraudulent design is a deviation from the accounting method that should be applied in an entity. Dishonesty can also occur because of other aspects related to accounting dishonesty, namely in regulations, people's etiquette, body customs and mental intellect. This research aims to identify the effects of regulatory effectiveness, people's etiquette, body habits and mental intelligence on accounting dishonesty tendencies. The population in this research is the employees of LPD Gianyar Regency with the illustrations used by 120 respondents. The data analysis method used in this research is multiple linear regression, coefficient of assurance, experiment t and experiment F. Based on the research results, it can be seen that: (1) the effectiveness of tax regulation in influencing the negative and significant to the tendency of accounting dishonesty, where the regression coefficient by -0.252 and sig 0.020.( 2) people's etiquette has a significant negative effect on accounting dishonesty tendencies, where the regression coefficient is -0, 311 and sig 0.009. (3) corporate customs have a significant negative effect on accounting dishonesty tendencies , where the regression coefficient is 0.321 and sig 0.021. (4) psychological intelligence has a significant minus effect on accounting dishonesty tendencies, where the regression coefficient is 0.144 and sig 0.017. The free elastic effect on accounting dishonesty bias is 52, 6%. Suggestions that can be submitted by researchers are the next researchers, so that they can examine and examine more deeply other factors that were not monitored in this research that could influence the tendency of the formation of accounting dishonesty.